PENGARUH STORE ATMOSPHERE DAN STORE LOCATION TERHADAP KEPUASAN KONSUMEN (Studi Pada Konsumen Produk Texas Chicken Plaza Citra Pekanbaru) - Masrul "; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine how much influence the store atmosphere and store location on customer satisfaction. Samples in this study were taken as many as 100 respondents and techniques used Inccidental Sampling approach. The data in this study using survey method through questionnaires filled by consumers. Data were obtained by using multiple regression analysis. From the results of this study shows the variable Store Atmosphere has a positive and significant impact on Consumer Satisfaction at Texas Chicken Plaza Citra Pekanbaru. And Store Locatin variables have a positive and significant impact on Consumer Satisfaction at Texas Chicken Plaza Citra Pekanbaru. Then simultaneously Store Atmosphere and Store Locatin positive and significant influence on Consumer Satisfaction at Texas Chicken Plaza Citra Pekanbaru. For further research it is suggested to increase the number of respondents in the sample calculation.Keywords: Store Atmosphere, Store Location, and Consumer Satisfaction